The Covid-19 Pandemic and Students’ Perception on the Online Case-Based Learning: The Case of One Online Course - Shofia Amin; Fitri Widiastuti; Sumarni (Universitas Jambi, Indonesia, 2022)
Case-based learning has been applied and proven to be effective in increasing students' class participation. However, studies on how this method is used through online learning are still limited. Whereas online learning activities have been done during the Covid-19 pandemic, but most students seem to become passive during an online class. This study investigated students’ perceptions of the case-based learning method and how this method could be effective. Using a mixed-method design, the data were collected through questionnaires in Google forms from 42 students of an online Change Management class and students were asked to write their thoughts and perceptions. The data, then, were analyzed using SPSS software. This study indicated that case-based learning is helpful for students’ academic and characters improvement. The students found the method beneficial because the lecturers implemented the method well. This study suggested that the key success of case-based learning in an online class depends on the lectures and the online learning facilities.